Residential location, workplace location and car driving in four Norwegian cities. Issue 10 (3rd October 2018) - Engebretsen, Øystein; Næss, Petter; Strand, Arvid
ABSTRACT: Based on a study in four Norwegian cities (Oslo, Stavanger/Sandnes, Bergen and Trondheim) differing in size and centre structure, this article illuminates how residential and workplace location, local-area density and transit accessibility influence different aspects of travel behaviour. We find strong effects of residential and workplace distance to the city centre on overall driving distances and commuting distances. We also find clear effects of local area densities around residences and workplaces on the choice of car as a travel mode, along with less pronounced effects of the distance from dwellings and workplaces to the city centre. In the cities with the best developed transit provision, we also see clear effects of transit accessibility at the residence on the propensity of choosing the car as travel mode. The results provide strong support of Norwegian national policies of urban densification as a planning strategy to curb the growth in urban motoring. However, although the influences of urban structure on travel show many similarities across the four cities, there are also important differences reflecting variations in centre structure (predominantly mono- or polycentric) and population size. The magnitude of the influences of various urban structural characteristics on travel behaviour are thus highly context-dependent.